What the COVID-19 Pandemic has Taught Me about Teaching Literature in Hong Kong. Issue 3 (3rd July 2021) - Chang, Hawk
ABSTRACT: Across the world, the COVID-19 pandemic has had far-reaching effects on many aspects of our everyday lives. Changes have also been apparent in the field of teaching since most teaching now has to be carried out online. Despite its drawbacks, this forced change to online instruction and learning has helped me reflect on my teaching. Based on my experience teaching literature at a university in Hong Kong, this article aims to highlight the lessons learned from the transformation caused by the pandemic.